A fluorescent conjugated polymer photocatalyst based on Knoevenagel polycondensation for hydrogen production. (18th April 2019) - Cao, Xinhua; Li, Yiran; Liu, Binqian; Gao, Aiping; Cao, Juntao; Yu, Yongsheng; Hei, Xiaohan
Abstract : An organic polymer photocatalyst (p-P ) for hydrogen production was designed and synthesized through Knoevenagel condensation with a high yield. Abstract : An organic polymer photocatalyst (p-P ) was designed and synthesized through Knoevenagel condensation between terephthalaldehyde and p -phenylenediacetonitrile with a high yield. The orangep-P polymer could emit pink light at 629 nm under excitation at 371 nm with a luminescence quantum yield of 2.57%. A cellular structure stacked by irregular polymer blocks was found in thep-P polymer with a small BET surface area of about 48.4 m 2 g −1 .p-P polymer was thermally stable up to 400 °C and possessed high charge separation efficiency and low resistance in charge transportation. DFT calculation and electrochemical experimental results indicated that the reduction reaction of water over the polymer is thermodynamically feasible.p-P polymer could efficiently split water under visible light irradiation with a prominent H2 production rate of up to 96.7 μmol g −1 h −1 and a TON of about 22.0. Our work provides a new strategy to build multifunctional conjugated polymers for efficient photocatalysis.